2022
DOI: 10.1177/1934578x221093916
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-Like Effect of Essential Oils From Citrus reticulata in Reserpine-Induced Depressive Mouse

Abstract: Citrus reticulata Blanco has been widely used to cure some diseases such as cold, cough and indigestion. This study is aimed at determining the antidepressant-like effect of C. reticulata essential oils (CREOs) in reserpine-induced depression mice, as well as its possible mechanisms. The compositions of CREOs are firstly analyzed by gas chromatography-mass spectrometry (GC-MS), in which d-limonene is the main component. Moreover, the results from the forced swimming and tail suspension tests show that the inha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
3
3
0
Order By: Relevance
“…The duration of immobility markedly decreased in animals administered a single dose of CBEO (25 mg/kg), indicating a rapid antidepressant effect. These results align with those of previous studies ( Tang et al, 2022 ; Tsai et al, 2023 ), although those studies required a longer treatment duration (one to six weeks) and higher doses (100–500 mg/kg for oral administration), suggesting an outstanding advantage of intranasal administration. Compared with other routes, intranasal delivery has been prominent in drug development in recent years owing to its rapid effects and high bioavailability by crossing the blood–brain barrier directly and avoiding the first-pass effect ( Shringarpure et al, 2021 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The duration of immobility markedly decreased in animals administered a single dose of CBEO (25 mg/kg), indicating a rapid antidepressant effect. These results align with those of previous studies ( Tang et al, 2022 ; Tsai et al, 2023 ), although those studies required a longer treatment duration (one to six weeks) and higher doses (100–500 mg/kg for oral administration), suggesting an outstanding advantage of intranasal administration. Compared with other routes, intranasal delivery has been prominent in drug development in recent years owing to its rapid effects and high bioavailability by crossing the blood–brain barrier directly and avoiding the first-pass effect ( Shringarpure et al, 2021 ).…”
Section: Discussionsupporting
confidence: 91%
“…The duration of immobility markedly decreased in animals administered a single dose of CBEO (25 mg/kg), indicating a rapid antidepressant effect. These results align with those of previous studies (Tang et al, 2022;Tsai et al, 2023), although those studies required a longer treatment duration (one to six weeks) and higher doses (100-500 mg/kg for oral administration), suggesting an outstanding advantage of intranasal administration.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Improvements in the neuroendocrine, neurotrophic, and monoaminergic systems are related to the antidepressant effects of limonene in mice [ 131 ]. A recent study demonstrated that C. reticulata essential oils (CREOs), which contain d -limonene as the main component, can serve as a potential therapeutic drug and food supplement against depression [ 132 ].…”
Section: Resultsmentioning
confidence: 99%
“…Value of p threshold = 0.05, k > 20 (number of voxels per cluster). Frontiers Nutrition 09 frontiersin.org models (14, 16,17,36,37). We can hypothesize that under acute stress our formulation and/or dosing may have not been sufficient to reduce significantly the emotional reactivity of FS animals.…”
Section: Behavioral Outcomes Of Chronic Exposure To the Functional In...mentioning
confidence: 99%